Prevalence and correlates of severe anxiety among front-line nurses during and after the COVID-19 pandemic: a large-scale multi-center study - Shutong Yang; Qingling Hao; Hongyu Sun; Yuan Yang; Jiao Liu; Cui Li; Yunsheng Fu; Cong Yao; Guoshuai Luo (BMC Nursing)
Abstract Background Nurses have been at the forefront of the battle against the COVID-19 pandemic, facing extended work hours and heightened stress, predisposing them to psychological distress. This study aims to investigate the prevalence and correlates of severe anxiety among frontline nurses in China during and after the COVID-19 pandemic. Methods A large-scale multi-center survey was conducted from November to December 2022 and from April to July 2023. Data were collected using online surveys, covering demographic characteristics, job-related factors, anxiety, depression, and sleep disorders. Statistical analyses, including chi-square tests, t-tests, and logistic regression, were performed to assess the incidence and factors influencing severe anxiety. Results The study included 816 nurses during the pandemic and 763 nurses after the pandemic. The prevalence of severe anxiety during the pandemic (52.3%) was significantly higher than after the pandemic (8.0%). Factors such as nursing title, night shift frequency, educational level, exercise frequency, COVID-19 infection status, economic pressure, and work pressure showed significant differences between the two periods. Binary logistic regression revealed associations between severe anxiety and factors such as night shift frequency, COVID-19 infection status, nursing title, depression, and sleep disorders. Receiver Operating Characteristic analysis demonstrated good predictive value for severe anxiety. Conclusion The study underscores the importance of understanding and addressing severe anxiety among frontline nurses during and after the COVID-19 pandemic. Future research should delve into long-term psychological effects and implement effective intervention measures to support nurses’ mental health.